KONSEP CORPORATE SOCIAL RESPONSIBILITY DALAM PERSPEKTIF KONVENSIONAL DAN FIQH SOSIAL - Santoso, Sugeng (Ahkam: Jurnal Hukum Islam, 2016)
The term”corporate social responsibility” (CSR) was firstly introduced in 1960 when A.B. Carrol addressed H.R. Bowen, the writer of a book entitled “Social Responsibilities of the Businessman” as the founding father of CSR. Since then, the theory of CSR has evolved for about five decades and been implemented by a number of corporate in many countries including Indonesia. Although CSR was developed from the Western perspectives, it turns out that it is matched with the Islamic perspectives. This paper discusses the concept of CSR from the Islamic perspectives and its implementation in business. The four principles of Islamic ethics, -unity, economic freedom, balance, and responsibility- might be developed into more descriptive principles so that they can be applied as the Islamic social and economic system. The ultimate goal of the Islamic social and economic system is to preserve the shariah (maqasid al shariah), respect the individuals, preserve the freedom of thinking, preserve the generation, and preserve the properties to achieve the prosperous and wealthy society. Kata kunci: Corporate Social Responsibility, Konvensional, Fiqh Sosial